CORRELATION BETWEEN FINE NEEDLE ASPIRATION CYTOLOGY AND CORRESPONDING ULTRASOUND BIRADS SCORE IN MAMMARY MALIGNANCY - ZAFAR, I; SAMAD, A; HAROON, A; FAYYAZ, N; FAYYAZ, N; MAHMOOD, N; BUKHARI, AA (Biological and Clinical Sciences Research Journal, 2022)
The aim of this study is to evaluate accuracy of ultrasound in diagnosing breast cancer and assessing correlation of radiological findings with findings of fine needle aspiration cytology (FNAC). Retrospective study was conducted at IbneSina Hospital& Multan Medical & Dental College Multan from July 2021 to December 2021. Study was conducted on 40 patients aged between 30 to 90 years having breast limps. Subjects underwent clinical and ultrasonic examination and BIRADS score was correlated with cytology data. Major ultrasonic finding was that irregular lesion was found in 21 (52.5%) subjects. In 10 (25%) patientsill defined lesion was found. FNAC revealed severe atypia in 7.5% and mammary carcinoma in 92.5% cases.BIRADS score V, IV and III were assigned to 75%, 20% and 5% cases respectively. Correlation of FNAC results with ultrasonic findings showed 90.6% accuracy of ultrasound in diagnosis of breast cancer. Ultrasonography provides accurate diagnosis of breast lesions and is recommended radiographic modality for assessing underlying cause of palpable breast mass.